Natural Compounds with Antifungal Properties against Candida albicans and Identification of Hinokitiol as a Promising Antifungal Drug - Louis Camaioni; Bastien Ustyanowski; Mathys Buisine; Dylan Lambert; Boualem Sendid; Muriel Billamboz; Samir Jawhara (MDPI AG, 2023)
Candida albicans is an opportunistic yeast that causes most fungal infections. C. albicans has become increasingly resistant to antifungal drugs over the past decade. Our study focused on the identification of pure natural compounds for the development of antifungal medicines. A total of 15 natural compounds from different chemical families (cinnamic derivatives, aromatic phenols, mono- and sesquiterpenols, and unclassified compounds) were screened in this study. Among these groups, hinokitiol (Hi), a natural monoterpenoid extracted from the wood of the cypress family, showed excellent anti-C. albicans activity, with a MIC value of 8.21 µg/mL. Hi was selected from this panel for further investigation to assess its antifungal and anti-inflammatory properties. Hi exhibited significant antifungal activity against clinically isolated fluconazole- or caspofungin-resistant C. albicans strains. It also reduced biofilm formation and hyphal growth. Treatment with Hi protected Caenorhabditis elegans against infection with C. albicans and enhanced the expression of antimicrobial genes in worms infected with C. albicans. Aside from its antifungal activities against C. albicans, Hi challenge attenuated the LPS-induced expression of pro-inflammatory cytokines (IL-6, IL-1β, and CCL-2) in macrophages. Overall, Hi is a natural compound with antifungal and anti-inflammatory properties, making Hi a promising platform with which to fight against fungal infections.